Kaidah-Kaidah Asasi Pendidikan dalam Perspektif Islam - Nurul Kamaliyah; Zaenal Arifin (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2021)
Education is a lifelong human need and cannot be separated from human life, which is critical to lead to development. Islamic education is a comprehensive and perfect legal principle. It can also make solutions and methods to grow children's personalities in creed, morals, physical, reason, mental and social. This article discusses the vital elements of education, how to do it, and who should do it. In this case, educators must be intelligent, perfect in mind, have good morals, and be physically strong, which is based on the essential characteristics of educators in education, including sincere in educating, piety to Allah SWT, knowledgeable, forgiving and forgiving, and carrying out the mandate as a responsibility. Thus an educator must know the rules in educating to be able to maintain self-image as an educator.